POLITENESS STRATEGIES USED BY SELENA GOMES AND ZACH IN ZACH SANG SHOWâ€™S INTERVIEW - Amelina, Nur; Astuti, Prihatin Puji (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
This thesis entitled â€œPoliteness Strategies Used by Selena Gomez and Zach in Zach Sang Showâ€™s Interviewâ€. The purpose of this study is to find the types of politeness strategies and the factors of using strategies by Selena and Zach. In analyzing the data, the writer used the theory of Brown & Levinson (1987) with a qualitative approach. The results of the research show that there are 39 data in politeness strategies used by Selena and Zach. They used 4 types of politeness strategies and 2 factors that influence the use of politeness strategies. The types of politeness strategies include 3 data bald on record, 29 data positive politeness, 4 data negative politeness, and 3 data off record. Politeness strategy that is most widely used is positive politeness. Positive politeness is a type of politeness strategy that can satisfy the listener’s positive face. Then there are 2 factors that influence the use of politeness strategies by Selena and Zach, namely the circumstances and payoff (results to be obtained). The payoff factor is the most widely used factor. This factor can support the use of politeness strategies in an interview